Canine facial eosinophilic furunculosis in a dog - Bindaco, Adriano Lima Stelzer; Monteiro, Lidianne Narducci; Sá, Mariana Marques; Reys, Marina Possa dos; Lobo, Renan Bernardo; Conti, Laura Monteiro de Castro; Flecher, Mayra Cunha (Brazilian Journal of Veterinary Pathology, 2022)
Canine facial eosinophilic furunculosis (FEF) is a hyperacute dermatopathy especially of the nasal bridge of dogs and is probably associated with type I hypersensitivity secondary to arthropod bites. The aim of this study is to report on a FEF case in a four-year-old female free-roaming mixed-breed dog showing papules on the nasal bridge that evolved to an ulcerated plaque. No other clinical, hematological, or biochemical alterations were detected. Cytology revealed eosinophilic and neutrophilic inflammation associated with bacterial infection. Punch biopsies were obtained for histopathological and microbiological analysis. Histopathology revealed marked, acute, multifocal to coalescent granulomatous eosinophilic furunculosis, and mild, acute, multifocal eosinophilic folliculitis. Microbiology revealed growth of coagulase-positive Staphylococcus sp. Clinical and histopathological findings were suggestive of facial eosinophilic folliculitis and furunculosis. Complete remission of the lesions was obtained after treatment. This condition is hyperacute, progressive, with a papular and erosive to ulcerative pattern, good prognosis, and its development is linked to arthropod bites. Furthermore, anti-inflammatory therapy is effective in treating the disease.